AB0528 Concomitant medication in systemic lupus erythematous (SLE) patients treated with belimumab in clinical practice settings: results from the observe study in switzerland. (12th June 2018) - von Kempis, J.; Dütsch, S.; Reuschling, N.; Schaer, D.; Vallelian, F.; Villiger, R.; Villiger, P.M.; Mueller, R.B.
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex and potentially severe autoimmune disease. Belimumab is the latest drug, and the first biologic compound, that was registered for treatment of SLE. There is limited information on safety and effectiveness of belimumab and its effects on the use of concomitant medication outside of randomised controlled trials. Objectives: To describe the overall patterns of SLE care, outcomes and concomitant medication among belimumab users in Switzerland. Methods: OBSErve Switzerland (GSK 201232) was a retrospective, multi-centre observational cohort study collecting data on the use of belimumab therapy in routine care of SLE Patients in Switzerland. SLE patients were included who had started therapy with 10 mg/kg belimumab/4 weeks at least six months before documentation. All patients were included regardless of treatment discontinuation during the study period. All statistical analyses were descriptive for both categorical and quantitative data. Results: 53 SLE patients with belimumab as part of their routine treatment were analysed for this study. 81% of the patients were female, the mean age was 46.7 years and the mean BMI was 25.4 kg/m 2 . The reasons to initiate belimumab were ineffective previous treatment (66.0%), worsening of patient condition (28.3%), and/or the intent to decrease glucocorticosteroid (GC) dose (47.2%). During treatment, 58% of patients (n=53) showed an improvement of ≥20% and 23% of ≥50%, based on physicians' evaluation of disease activity. This was consistent with an improvement of SELENA-SLEDAI (mean) from 8.0 at therapy start to 3.6 after six months on the basis of all available data (n=27). Similar outcomes were observed for arthritis, fatigue, rash, dsDNA antibody and complement levels. Among the 42 patients treated with GC at time of belimumab initiation, GC dose was reduced by 5.7 mg/day (mean) during treatment with belimumab (11.6≥5.9 mg/day at six months). During the six months before initiation of belimumab, GC dose was stable or had to be increased in the majority of patients; however, during the six months therapy with belimumab, GC dose could be reduced in the majority of patients and GCs was discontinued in two patients. The percentages of patients receiving SLE co-medication other than GC were stable over the first six months of belimumab therapy. Within the first six months of treatment, no included patient had discontinued therapy with belimumab. Conclusions: Treatment with belimumab over six months after initiation led to clinical improvement in a significant number of patients in real life settings and had an overall steroid-sparing effect. Belimumab was well-tolerated; no included patient discontinued the treatment within the first six months. Acknowledgements: COMMERCIAL SUPPORT GRANT DISCLOSURE: Research funded by GlaxoSmithKline, UK. Disclosure of Interest: J. von Kempis: None declared, S. Dütsch Employee of: SD is an employee of GSK, N. Reuschling: None declared, D. Schaer: None declared, F. Vallelian: None declared, R. Villiger: None declared, P. Villiger: None declared, R. Mueller: None declared